Investigation on Characteristics of 3–5 μm Mid-Infrared Optical Parametric Amplification in LiInS2 - Jingjing Zhang; Feng Yang; Yuanzhai Xu; Hongwei Gao; Yong Bo (IEEE Photonics Journal, 2024)
The optical parametric amplification process in the mid-infrared (MIR) 3–5 μm region of nonlinear crystal LiInS2 (LIS) has been investigated. The LIS crystal was pumped by a 1064 nm laser with a pulse width of 30 picoseconds and seeded by a tunable laser generated from a KTP-OPG/OPA pumped by the second harmonic (SH) of the same 1064 nm laser. In the experiment, the 3.28–5.50 μm tunable idler was realized. When the fixed pump energy is 8.75 mJ, the idler energy obtained is 72.2 μJ at 3.28 μm and 63.3 μJ at 5.50 μm. The maximum idler energy of 179.4 μJ at 4.70 μm is reached at a pump energy of 12.5 mJ, and the optimal photon conversion efficiency is 6.36% at the pump energy of 11.5 mJ. Finally, the optical parametric frequency conversion parameters and performance in the 3–5 μm of several typical new crystals (BGSe, LISe, AGS, HGS, and LGS) developed in recent years are briefly compared and summarized.